Identification, expression and characterization of rat isoforms of the serum response factor (SRF) coactivator MKL1. Issue 1 (7th September 2013) - Ishikawa, Mitsuru; Shiota, Jun; Ishibashi, Yuta; Hakamata, Tomoyuki; Shoji, Shizuku; Fukuchi, Mamoru; Tsuda, Masaaki; Shirao, Tomoaki; Sekino, Yuko; Ohtsuka, Toshihisa; Baraban, Jay M.; Tabuchi, Akiko
Abstract : Megakaryoblastic leukemia 1 (MKL1) is a member of the MKL family of serum response factor (SRF) coactivators. Here we have identified three rat MKL1 transcripts: two are homologues of mouse MKL1 transcripts, full‐length MKL1 (FLMKL1) and basic, SAP, and coiled‐coil domains (BSAC), the third is a novel transcript, MKL1‐elongated derivative of yield (MELODY). These rat MKL1 transcripts are differentially expressed in a wide variety of tissues with highest levels in testis and brain. During brain development, these transcripts display differential patterns of expression. The FLMKL1 transcript encodes two isoforms that utilize distinct translation start sites. The longer form possesses three actin‐binding RPXXXEL (RPEL) motifs and the shorter form, MKL1met only has two RPEL motifs. All four rat MKL1 isoforms, FLMKL1, BSAC, MKL1met and MELODY increased SRF‐mediated transcription, but not CREB‐mediated transcription. Accordingly, the differential expression of MKL1 isoforms may help fine‐tune gene expression during brain development. Abstract : Megakaryoblastic leukemia 1 (MKL1) is a serum response factor (SRF) coactivator. We have identified multiple rat MKL1 isoforms, including a novel one named MELODY. Rat MKL1 isoforms are enriched in testis and brain. Expression of rat MKL1 isoforms is regulated during brain development. All rat MKL1 isoforms act as SRF transcriptional coactivators.